Pandora's box in the dental clinic. (20th June 2022) - Ben-David, Debby; Vaturi, Azza; Solter, Ester; Rubinovitch, Bina; Lellouche, Jonathan; Schwartz, David; Schechner, Vered; Carmeli, Yehuda; Schwaber, Mitchell J.
Abstract: Background: In June 2018, the Ministry of Health received notification from 2 hospitals about 2 patients who presented with overwhelming Enterobacter kobei sepsis that developed within 24 hours after a dental procedure. We describe the investigation of this outbreak. Methods: The epidemiologic investigation included site visits in 2 dental clinics and interviews with all involved healthcare workers. Chart reviews were conducted for case and control subjects. Samples were taken from medications and antiseptics, environmental surfaces, dental water systems, and from the involved healthcare professionals. Isolate similarity was assessed using repetitive element sequence-based polymerase chain reaction (REP-PCR). Results: The 2 procedures were conducted in different dental clinics by different surgeons and dental technicians. A single anesthesiologist administered the systemic anesthetic in both cases. Cultures from medications, fluids and healthcare workers' hands were negative, but E. kobei was detected from the anesthesiologist's portable medication cart. The 2 human isolates and the environmental isolate shared the same REP-PCR fingerprinting profile. None of the 21 patients treated by the anesthesiologist in a general hospital during the same period, using the hospital's medications, developed infection following surgery. Conclusions: An outbreak of post–dental-procedure sepsis was linked to a contaminated medication cart, emphasizing the importance of medication storage standards and strict aseptic technique when preparing intravenous drugs during anesthesia. Immediate reporting of sepsis following these outpatient procedures enabled early identification and termination of the outbreak.